2006
DOI: 10.1111/j.1439-037x.2006.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Activity of Stylosanthes guianensis and its Phytotoxic Components

Abstract: Stylosanthes guianensis is a popular pasture legume and cover crop. The legume possessed strong allelopathic potential and suppressed spontaneous growth of paddy weeds. In a bioassay, aqueous extract of S. guianensis remarkably inhibited germination and growth of barnyardgrass and monochoria. Application of 1 ton ha )1 upland parts of S. guianensis significantly reduced paddy weed biomass by 80 % and increased rice yield by 40 % when compared with the control. Gas chromatography-mass spectrometry analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In the same context, confertiorin isolated from Ambrosia confertifora has been reported to inhibit the germination of Amaranthus palmeri and Amaranthus retrofexus (Fischer & Mabry, 1985). Moreover, Khanh et al (2006) proved that Stylosanthes guianensis showed significant herbicidal effects against Echinochloa crus-galli and Monochoria vaginalis. They attributed its phytotoxicity to the presence of several allelochemicals in S. guianensis including phenolic acids, coumarin and long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 94%
“…In the same context, confertiorin isolated from Ambrosia confertifora has been reported to inhibit the germination of Amaranthus palmeri and Amaranthus retrofexus (Fischer & Mabry, 1985). Moreover, Khanh et al (2006) proved that Stylosanthes guianensis showed significant herbicidal effects against Echinochloa crus-galli and Monochoria vaginalis. They attributed its phytotoxicity to the presence of several allelochemicals in S. guianensis including phenolic acids, coumarin and long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that the application of plants with strong allelopathic properties as a natural herbicide for weed management and reducing the reliance on chemical herbicides could be a feasible solution (Khanh et al 2006). Allelopathy is defined as an interaction among plants by chemical pathways.…”
Section: Allelopathic Effect Of Methanol Extracts From Tinospora Tubementioning
confidence: 99%
“…Applying kava root ( Piper methysticum L.) (Xuan et al . 2003), Stylosanthes guianensis Sw. (Khanh et al . 2006), Saururaceae ( Houttuynia cordata Thunb) (Lin et al .…”
mentioning
confidence: 99%